Dihydroxy hydroxylamine modified polysiloxane as well as preparation method and application thereof

By converting the primary amino group of amino silicone oil into bishydroxyhydrocarbonyl or carboxyl-containing bishydroxyhydrocarbonyl amino silicone oil, and using bishydroxyhydroxyhydrocarbonyl-modified polysiloxane, the problems of oxidation and yellowing of the amino-modified silicone softener and uneven distribution of functional groups are solved, achieving efficient finishing and durability of the fabric.

CN119798675APending Publication Date: 2025-04-11HANGZHOU NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411978747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The amino-modified silicone softener is prone to oxidation and yellowing after use, resulting in a decrease in the whiteness of the fabric and the uneven distribution of functional groups, which affects the fabric finishing effect and hydrophilicity.

Method used

The primary amine group of the amino silicone oil is converted into bishydroxyhydrocarbonyl or carboxyl group-containing bishydroxyhydrocarbonyl amino silicone oil, and the antistatic, hydrophilicity and yellowing resistance of the fabric are improved through ether bond modification.

Benefits of technology

It significantly improves the antistatic, hydrophilic and yellowing resistance of the fabric, improves the overall performance of the fabric, and enhances the application effect of the softener.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798675A_ABST
    Figure CN119798675A_ABST
Patent Text Reader

Abstract

The invention discloses dihydroxyhydroxylamine modified polysiloxane as well as a preparation method and application thereof. The polysiloxane has a structure as shown in any one of formulas I-III. The oxidation yellowing resistance of a tertiary amine structure formed by a primary amine group of amino silicon oil is superior to that of primary amine, hydrogen bonds can be formed between introduced hydroxyl and water molecules, better hygroscopicity can be brought to fabric, the problems of yellowing and poor hydrophilicity caused by modification of amino silicon oil are solved, and when the amino silicon oil is used for treating the fabric, the service life of the fabric is prolonged. The antistatic performance, the hydrophilicity, the yellowing resistance and the like of the woven fabric are obviously improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polysiloxane materials, and in particular to a dihydroxyhydroxylamine-modified polysiloxane and a preparation method and application thereof. Background Art

[0002] Polysiloxane materials are a class of polymers with repeated Si-O bonds as the main chain and organic groups directly connected to silicon atoms. The main chain of polysiloxane with methyl as the common organic group is very flexible, and the energy required to rotate around the Si-O bond is almost zero, giving the polysiloxane chain freedom, so that the polysiloxane chain can rotate 360 ​​degrees freely. Thanks to the rotational freedom of the Si-O-Si bond and the low interaction energy between the methyl groups on the silicon atoms, organosiloxane has good low surface tension, electrical properties, softness and thermal oxidation stability, which make organosiloxane an excellent fabric finishing agent. The unique structure of polysiloxane is applied to fabric finishing agents to provide fabrics with good force resilience and flexibility. Introducing other functional groups into the organosilicon chain can further improve the application performance of organosilicon softeners. Compared with other functional group modifications, aminoalkyl is often used to chemically modify the polysiloxane main chain, which can give polysiloxane the so-called "super soft" treatment effect.

[0003] Fabrics treated with amino-modified silicone generally show good softness, flexibility, tensile strength, and color fastness. Amino-modified silicone softeners are called "the king of softeners" because of their excellent properties. They give fabrics better softness, feel, and yellowing resistance. Fabric softening finishing agents have become important additives for textile processing. Fabric softening finishing agents can reduce the friction coefficient between fibers, making the fabric surface soft. Silicone softeners are the most widely used and fastest growing softeners on the market.

[0004] Amino-modified silicone softeners have a long history, and amino-modified silicones can bring excellent softness and feel to fabrics. Therefore, most finishing agents still use amino-modified silicones as materials. However, amino-modified silicone softeners still have the following problems after being used for fabric treatment:

[0005] 1. Yellowing due to oxidation: The nitrogen atom in the amino group is very easy to oxidize under heat or ultraviolet radiation (generating yellowing groups such as azo or oxyazo), and amino silicone will also affect the strength of the textile whitening agent and its maximum emission wavelength, resulting in a decrease in the whiteness of the fabric; 2. Uneven distribution of amino groups: During the preparation process of amino-modified silicone, there may usually be uneven distribution of functional groups in the polysiloxane chain segments. In this case, the groups containing amino groups will be tightly bound to the surface of the fabric, while the functional groups without amino groups will not be firmly bound to the fabric, resulting in easy gelation during the reaction preparation, and demulsification and oil floating during emulsification; 3. Amino groups lead to poor hydrophilicity: In addition to intermolecular forces, electrostatic forces and van der Waals forces, hydrogen bonds are also formed at the interface of amino-modified silicone and cellulose.

[0006] Khalid et al. (Zia KM, Tabassum S, Barkaat-ul-Hasin S, et.al. Preparation of rich handles soft cellulosic fabric using amino silicone based softener. Part-I: Surface smoothness and softness properties [J]. International Journal of Biological Macromolecules, 2011, 48 (3): 482-487.) studied the effect of amino-modified silicone softener on the surface properties of cotton fabric. They found that amino-modified silicone softener can form a hydrophobic polymer coating on the surface of cotton fabric, thereby reducing the surface roughness. As the intensity of amino-modified silicone softener applied increases, the surface roughness is further reduced. These results show that amino-modified silicone softener can effectively improve the surface properties of cotton fabric.

[0007] Islam et al. (Islam MS, Lahiri SK, Nahar J, et al. Synthesis and application of amino-modified silicone oil on cotton fabric [J]. International Journal of Scientific and Engineering Research, 2015, 6 (5): 1195-1203.) prepared amino-modified silicone, emulsified it and applied it to fabric finishing and tested its performance. The emulsion (solid content of 25%, pH of 6-7, viscosity of 60 mPa·s) can still have thermal stability, alkali stability and dielectric stability at a high temperature of 80°C. The test performance found that the amino-modified silicone softener has little effect on the strength of the fabric, and has no significant effect on the color fastness of the dyed fabric, which can give the fabric good wash resistance. After multiple washings, the color retention rate is 60%, and the softness test rating reaches 5 (the feel rating of the original cotton fabric is 4.5).

[0008] However, the hydrophilicity, fabric softness and yellowing resistance of amino-modified polysiloxane used as silicone softener still need to be further improved. Summary of the invention

[0009] Aiming at the problem that the yellowing resistance of amino-modified polysiloxane as a softener still needs to be improved, the present invention provides a polysiloxane modified with a dihydroxyhydroxylamine group, in which the primary amine group of amino silicone oil is converted into a dihydroxy hydrocarbon group or a carboxyl-containing dihydroxy hydrocarbon amino silicone oil, thereby improving and solving the yellowing and poor hydrophilicity problems of silicone softeners.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] A dihydroxyhydroxylamine-modified polysiloxane having a structure as shown in any one of Formulas I-III:

[0012]

[0013] Among them, R1 is * represents the site of connection with Si, n is a natural number of 8-64, m is a natural number of 20-50, and x: (162+60x+74y)=0.09-0.75%.

[0014] The tertiary amine structure formed by the primary amine group of the amino silicone oil in the present invention has better resistance to yellowing due to oxidation than the primary amine, and the introduced hydroxyl group can form hydrogen bonds with water molecules, which can bring better hygroscopicity to the fabric, improve the yellowing and poor hydrophilicity of the amino silicone oil, and be used to treat fabrics to significantly improve the antistatic properties, hydrophilicity and yellowing resistance of the fabrics. Due to the differences in the properties of the functional groups, the monofunctional silicone softener can only meet the specific or partial requirements of fabric processing. In order to obtain a silicone finishing agent with better comprehensive effects, a multifunctional modified silicone softener is essential.

[0015] The present invention also provides a carboxyl-containing bishydroxylamine-modified polysiloxane having a structure as shown in any one of Formulas I to III above,

[0016] Among them, R1 is * represents the connection site with Si, and n, m, x, and y are as described in claim 1.

[0017] Through further grafting, chemical functional groups such as carboxyl and ester groups can be grafted into polysiloxane to improve the mechanical properties of the fabric.

[0018] The number average molecular weight of the polysiloxane represented by formula I is 1000 to 5000 g / mol, and the PDI value is 1.6 to 2.4;

[0019] The number average molecular weight of the polysiloxane represented by formula II is 2000 to 4000 g / mol, and the PDI value is 1.90 to 2.50;

[0020] The number average molecular weight of the polysiloxane represented by formula III is 500-5000 g / mol, and the PDI value is 1.6-3.2.

[0021] The present invention also provides a method for preparing the dihydroxyhydroxylamine-modified polysiloxane, comprising the steps of:

[0022] Step 1, reacting allyl glycidyl ether with any hydrogen-containing polysiloxane represented by any one of M1-M3 to perform a hydrosilylation reaction to obtain any one of the intermediates M4-M6;

[0023] Step 2, reacting any compound among the intermediates M4-M6 with 2-ethylaminoethanol to obtain the dihydroxyhydroxylamine-modified polysiloxane;

[0024]

[0025] Where R2 is * represents the connection site with Si, and n, m, x, and y are as described in claim 1.

[0026] In step 1, a Karstedt catalyst is added to catalyze the reaction. The effective amount of palladium in the Karstedt catalyst is 5 to 30*10 of the total mass of the raw material. -6 ppm;

[0027] Before the reaction, the Custer catalyst and allyl glycidyl ether were mixed and activated at 50-80°C for 15-40 minutes;

[0028] The hydrosilylation reaction temperature of step 1 is 60-80°C and the reaction time is 6-8h;

[0029] The reaction in step 2 is carried out at 80-120° C. for 2-8 hours;

[0030] In step 1, the molar ratio of the double bond in allyl glycidyl ester to the silicon-hydrogen bond in the hydrogen-containing polysiloxane represented by any one of M1 to M3 is 1-1.2:1.

[0031] The present invention also provides a method for preparing the carboxyl-containing bishydroxyhydroxyamine-modified polysiloxane, comprising the steps of: reacting the bishydroxyhydroxyamine-modified polysiloxane according to claim 1 with glutaric anhydride to obtain the carboxyl-containing bishydroxyhydroxyamine-modified polysiloxane.

[0032] The reaction temperature with glutaric anhydride is 80-120°C and the reaction time is 2-8h.

[0033] The molar ratio of the R1 group to glutaric anhydride in the dihydroxyhydroxylamine-modified polysiloxane is 1:2-3.

[0034] The invention also provides a modified polysiloxane emulsion, which is obtained by emulsifying the modified polysiloxane.

[0035] The present invention also provides a method for preparing the modified polysiloxane emulsion, comprising the steps of: mixing 1-5 parts of the modified polysiloxane, 0.1-2 parts of the composite catalyst, 0.01-0.5 parts of acetic acid and 5-15 parts of the mixture for phase inversion; diluting the emulsion after phase inversion with water at a mass ratio of 5-15:200 to obtain the modified polysiloxane emulsion;

[0036] The composite catalyst is a mixture of AE0-6 and AEO-9, and the mass concentration of acetic acid is 20-40%.

[0037] The present invention also provides the use of the modified polysiloxane emulsion as an organosilicon softener in fabrics, comprising the steps of: immersing the fabric in the modified polysiloxane emulsion for 5-30 seconds, and obtaining the softened fabric through shaping and drying.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The bishydroxylamine-modified polysiloxane in the present invention contains ether bonds, and has better antistatic properties than bishydroxylamine-modified polysiloxane without ether bonds, because the ether bonds are beneficial to the release of static charges on the fabric, thereby improving the antistatic ability.

[0040] (2) The ether bond-modified bis(hydroxyalkylamine) polysiloxane in the present invention has better hydrophilicity than bis(hydroxyalkylamine) polysiloxane, because the ether bond is conducive to reducing the tension of the liquid on the surface of the fabric, thereby improving the surface hydrophilicity.

[0041] (3) The ether-modified bishydroxyalkylamine polysiloxane emulsion of the present invention and the woven fabric are placed on a padder for a padding process, and the hydrophilicity of the woven fabric is greatly improved, and the yellowing resistance is also slightly improved.

[0042] (4) Introducing other functional groups containing carboxyl or ester groups into the bishydroxyalkylamine-modified polysiloxane of the present invention can bring about different performance improvements. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The single-end glycidoxypropyl functionalized polydimethylsiloxane prepared from S1 of Example 1 1 H NMR spectrum.

[0044] Figure 2 The ether-modified single-terminated bis-hydroxyalkylamine polysiloxane (I) of Example 1 1 H NMR spectrum.

[0045] Figure 3 The ether bond modified double-terminated bis-hydroxylamine polysiloxane material (II) prepared in Example 2 1 HNMR spectrum.

[0046] Figure 4 The side chain ether bond modified bishydroxyalkylamine polysiloxane material (III) prepared in Example 3 1 HNMR spectrum.

[0047] Figure 5 Preparation of carboxyl and ether bond modified single-terminated bishydroxyalkylamine polysiloxane (I-1) for Example 4 1 HNMR spectrum.

[0048] Figure 6 Preparation of carboxyl and ether bond modified double-terminated bishydroxyalkylamine polysiloxane (II-1) for Example 5 1 HNMR spectrum.

[0049] Figure 7 The single-terminated bishydroxyalkylamine polysiloxane (IV) prepared in Comparative Example 1 without ether bond modification 1 HNMR spectrum.

[0050] Figure 8 This is a comparison chart of the softness of the ether bond modified single-terminal bishydroxyalkylamine polysiloxane prepared in Example 1 and the unmodified single-terminal bishydroxyalkylamine polysiloxane.

[0051] Fig. 9 This is a comparison chart of the hydrophilicity of the ether bond modified single-terminated bis-hydroxyalkylamine polysiloxane prepared in Example 1 and the unmodified single-terminated bis-hydroxyalkylamine polysiloxane. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0053] The raw materials used in the following specific embodiments are all purchased from the market.

[0054] Example 1 Single-end modified bishydroxyalkylamine polysiloxane (I) was prepared according to the following steps:

[0055] S1: 10 mL of toluene, 0.17 g of 2,6-di-tert-butyl-p-cresol (BHT) and 1.6 g of allyl glycidyl ether were added to a 50 mL three-necked flask under dry nitrogen protection, and then 0.16 g of 0.1 wt % Karstedt catalyst (effective palladium content 10 ppm) was added, and activated at 70°C for 30 min; 15 g of single-end hydrogenated polysiloxane (M1) (Mn≈1400 g / mol) was injected into the reaction solution using an injection pump, and the injection time was 1.5 h. After the injection, the reaction was continued at 70°C for 2 h to terminate the reaction to obtain the product single-end glycidoxypropyl functionalized polydimethylsiloxane (M4), with a yield of 94%.

[0056] By changing the molecular weight of the single-end hydrogen-containing polysiloxane (M1), single-end glycidoxypropyl functionalized polydimethylsiloxane (M4) with different molecular weight distributions are obtained as shown in Table 1. EP-1 to EP-5 represent the sample numbers of single-end glycidoxypropyl functionalized polydimethylsiloxane (M4) with different molecular weights.

[0057] Table 1 Synthesis data of single-end glycidoxypropyl functionalized polydimethylsiloxane

[0058]

[0059] Note: Mn is the molecular weight, all molecular weights are approximate values; n PMPS-H is the molar amount of single-ended hydrogen-containing silicone oil, nC=C Refers to the molar mass of allyl glycidyl ether, w cat Refers to Custer catalyst, w prod Refers to the mass of product M4.

[0060] S2: 10 g of single-end glycidoxypropyl functionalized polydimethylsiloxane (M4) (Mn≈1500 g / mol) and 0.94 g of 2-ethylaminoethanol were reacted at 100°C for 4 hours, and after the oil pump was decompressed for 3 hours, the product single-end ester-modified bis-hydroxyalkylamine polysiloxane material (I) was obtained with a yield of 87%. A series of ether-modified single-end bis-hydroxyalkylamine polysiloxanes with molecular weights of about 1000 g / mol, 1500 g / mol, 2500 g / mol, 4000 g / mol, and 5000 g / mol were synthesized using M4 with different molecular weights.

[0061] Calculation and test: With single-terminal hydrogenated silicone oil as the key component, the single-terminal glycidoxypropyl functionalized polydimethylsiloxane product (M4) with a molecular weight of about 1500 prepared by hydrosilylation in Example 1 was calculated and tested. 1 H NMR analysis: Chemical shift δ = 0.5 ppm is near methylene Si-C H The characteristic peak of 2-CH2-, δ=0.8ppm is Si-CH2-C H Characteristic peak of 2-, characteristic peak of ether bond modification -C H 2-OC H 2-Chemistry At displacement δ = 3.5 ppm, epoxy-CH-C H The chemical shift of 2- is affected by the electronegativity of oxygen atoms and splits, appearing at δ = 2.5ppm and 2.8ppm. The characteristic peak of epoxy -C H -CH2- defines the characteristic peak Si-C of hydrosilylation at the chemical shift δ = 3.1 ppm H The peak area of ​​2-CH2- is 2.0, and the areas of other peaks are consistent with the structural characteristics. The molecular weight Mn calculated by NMR is 1536 g / mol. The NMR results are in line with expectations, proving that the target product - single-end glycidoxypropyl functionalized polydimethylsiloxane - was obtained.

[0062] Single-end glycidoxypropyl functionalized polydimethylsiloxane (M4) 1 H NMR results are as follows Figure 1 As shown. Among them, the ether bond modification characteristic peak -C H 2-OC H The integral ratio of the characteristic peaks of the structure generated by the addition reaction of 2- (~3.5ppm) and hydrosilylation (~0.5ppm) is 4.2:2.0. The characteristic peak of hydrosilylation (SiCH2) and the characteristic peak of epoxy function (-C H-CH2-) ratio is 2.0:1.0, indicating that the epoxy structure has not changed during the addition process. 1 The degree of polymerization of the polymer was calculated from H NMR integration to be n≈17.8.

[0063] The results of ether bond modified single-terminal dihydroxylamine polysiloxane (I) are as follows Figure 2 As shown, the chemical shift δ = 0.5 ppm is methylene Si-C H The characteristic peak of 2-CH2-, chemical shift δ = 1.1ppm is Si-CH2-C H Characteristic peaks of 2-. Alkylamine-NC H 2-C H The chemical shifts of 3 are at δ = 2.7 and 1.1 ppm, and the peak at 1.1 ppm corresponds to Si-CH2-C H The characteristic peaks of 2- overlap. Bishydroxyalkylamine -CH(OH)-CH-C H 2-NC H The chemical shift of 2-CH2-OH overlaps at δ = 2.8 ppm. H The chemical shift of 2-CH(OH)- is affected by the electronegativity of the oxygen atom and moves downfield to appear at δ≈4.0ppm, while -C H The characteristic peak of 2-O-CH2-CH(OH)- is consistent with the -N-CH2-C H The characteristic peak of 2-OH overlaps and appears at a chemical shift of 3.4 ppm. H The peak appears as a broad bulge in NMR, with a chemical shift at 2.2ppm. H 3 Chemical shift appears at 0.08ppm. Definition of methylene Si-C H The peak area of ​​2-CH2- is 2, and the other peaks are consistent with the structural characteristics of ether bond modified single-terminated bishydroxyalkylamine polysiloxane (I). Figure 2 It is an ether-modified single-terminated dihydroxyalkylamine polysiloxane with a polymerization degree of n≈12. The molecular weight M is calculated by NMR. NMR =1273 g / mol.

[0064] Example 2

[0065] According to the process of Example 1, in step 1, the single-terminal hydrogen-containing polysiloxane is replaced with a double-terminal Si-H polysiloxane shown in formula M2, and the other steps are the same to obtain a double-terminal bis-hydroxylamine-modified polysiloxane (II) shown in formula II. The NMR spectrum of the product is shown in Figure 3 shown.

[0066] Example 3

[0067] According to the process of Example 1, in step 1, the single-terminal hydrogen-containing polysiloxane is replaced with a double-terminal Si-H polysiloxane with a hydrogen content of 0.09-0.75% as shown in formula M3, and the other steps are consistent to obtain an ether bond-modified side chain bishydroxyalkylamine-modified polysiloxane as shown in formula (III). The NMR spectrum of the product is shown in Figure 4 shown.

[0068] Example 4

[0069] The ether bond modified single-terminal bis-hydroxylamine polysiloxane obtained in Example 1, i.e., product (I), was reacted with glutaric anhydride, wherein the amount of glutaric anhydride was twice that of the ether bond modified single-terminal bis-hydroxylamine polysiloxane, the reaction temperature was 100°C, and the reaction time was 4 hours. Carboxyl groups were introduced without other additives or solvents to achieve the preparation of single-terminal bis-hydroxylamine polysiloxane (I-1) modified with ether bonds and carboxyl functional groups. The NMR spectrum of the product is shown in FIG. Figure 5 shown.

[0070]

[0071] Example 5

[0072] The ether bond modified double-terminal bis-hydroxylamine polysiloxane obtained in Example 2, namely product (II), was reacted with glutaric anhydride, wherein the amount of glutaric anhydride was twice that of the ether bond modified single-terminal bis-hydroxylamine polysiloxane, the reaction temperature was 100°C, and the reaction time was 4 hours. Carboxyl groups were introduced without other additives or solvents to achieve the preparation of the double-terminal bis-hydroxylamine polysiloxane (II-1) modified with ether bonds and carboxyl functional groups. The NMR spectrum of the product is shown in FIG. Figure 6 shown.

[0073]

[0074] Comparative Example 1: Single-ended unether-modified dihydroxyhydroxylamine polysiloxane

[0075] S1: Add 158g (1.5mol) of diethanolamine to a dry 500mL three-necked round-bottom flask equipped with a magnetic stirrer, a condenser, a thermometer and a constant pressure dropping funnel, and slowly add 314g (1.95mol) of hexamethyldisilazane under stirring and reflux at 100°C for 225min. After the addition is completed, the temperature is raised to 140°C at 10°C / h, and the heating is turned off after reflux and stirring for 30h. The product bis[2-(trimethylsilyloxy)ethyl]amine is distilled out at 140°C under reduced pressure of 100kpa as a transparent liquid with a yield of 93%.

[0076] S2: 49.8g of bis[2-(trimethylsilyloxy)ethyl]amine was added to a dry 250mL three-necked round-bottom flask with a magnetic stirrer, a condenser, a thermometer and a constant pressure dropping funnel. 25.4g of allyl bromide was slowly added dropwise under an ice bath at 5°C. After the addition, the yellow color of the solution became more obvious. After the ice cubes were removed, the temperature gradually returned to room temperature and was placed in a 40°C oil bath. A 20% NaOH solution was slowly added dropwise to make the whole system in a weakly alkaline state. The reaction proceeded in the positive direction. After all the additions were completed, the reaction was terminated after 2 hours. The oil phase extracted with dichloromethane was desolventized and distilled under a pressure reduction of 100kpa. The single-terminal hydrogenated silicone oil of the N,N-bis[2-(trimethylsilyloxy)ethyl]allylamine product at 140°C was collected. The GC-MS purity was 99% and the yield was 51.2%.

[0077] S3: Add 15 ml of toluene with a water content of 200 ppm and 1.09 g (3.76 × 10 -3 mol) of N,N-bis[2-(trimethylsilyloxy)ethyl]allylamine, 0.38g of 1wt% karstedt catalyst (effective content is 230ppm), stirred and heated to 70°C, and activated at this temperature for 30min; 15.5g of single-ended hydrogenated silicone oil was uniformly added to the reaction system using a syringe pump, and the injection time was 1.5h. After the injection was completed, the reaction was continued at 70°C for 10h and then cooled to room temperature. The system was left open to deactivate the catalyst, and the product was subjected to reduced pressure distillation to remove low boiling points to obtain α-methyl-ω-N,N-bis[2-(trimethylsilyloxy)ethyl]aminopropyl polydimethylsiloxane.

[0078] Taking the synthesis of α-methyl-ω-N,N-dihydroxyethylaminopropyl polydimethylsiloxane with a molecular weight of Mn 1000 as an example, the raw material conversion rate is greater than 90%. Add acetic acid-methanol (1:50) mixture and reflux for 6 hours, remove low-boiling substances to obtain the target single-terminal dihydroxyalkyl-modified aminopolysiloxane (α-methyl-ω-N,N-dihydroxyethylaminopropyl polydimethylsiloxane) shown in formula IV. The double bonding rate of the emulsifiable single-terminal dihydroxyalkyl-modified aminopolysiloxane is close to 100%, and the yield is 90%. After deprotection, the target single-terminal dihydroxyalkyl-modified aminopolysiloxane material is obtained, and the nuclear magnetic resonance spectrum of the product with a molecular weight of about 1000 is as follows Figure 7 shown.

[0079]

[0080] The data of α-methyl-ω-N,N-bis[2-(trimethylsiloxy)ethyl]aminopropyl polydimethylsiloxane with different molecular weights are shown in Table 2. OH-1 to OH-5 represent the sample numbers of α-methyl-ω-N,N-bis[2-(trimethylsiloxy)ethyl]aminopropyl polydimethylsiloxane (Ⅰ) with different molecular weights. Mn / g·mol -1 Refers to the relative number average molecular weight of the sample obtained by GPC test; η 25 / cP is the viscosity value of the test sample at 25°C; n D 25 Av is the refractive index of the test sample at 25°C; b / mmol·g -1 is the ammonia value obtained by titration, and b is the monomer containing a C=C bond. It can be seen that the higher the molecular weight, the more difficult it is to synthesize.

[0081] Table 2 Data of single-terminal dihydroxyalkylamine polysiloxanes with different molecular weights that are not modified by ether bonds

[0082] Sample name <![CDATA[Mn / g·mol -1 ]]> <![CDATA[η 25 / cP]]> <![CDATA[n D 25 ]]> <![CDATA[Av b / mmol·g -1 ]]> Yield % OH-1 1000 111.5 1.4147 1.57 90% OH-2 1500 142.6 1.4146 0.64 88% OH-3 2500 204.3 1.4045 0.52 75% OH-4 4000 207.5 1.4125 0.25 72% OH-5 5000 245.0 1.4041 0.18 64%

[0083] Application Example 1 Preparation of a Silicone Softener Emulsion

[0084] Take 2g of polysiloxane, 0.6g of emulsifier D-1 (D-1 is a composite emulsifier, prepared by mixing fatty alcohol polyoxyethylene ether AE0-6 and AEO-9 in a mass ratio of 1:1), 0.1g of 33% acetic acid, and 7.3g of water for preliminary phase inversion. After the phase inversion, take 6g and add 200g of water for dilution to obtain an O / W emulsion (O / W refers to oil-in-water state) with a solid content of 20%.

[0085] Calculation and testing:

[0086] Cutting fabric: The fabric should be woven fabric and the cutting size should be the size of two A4 papers.

[0087] Padding: Soak the tested woven fabric in the emulsion for 10 seconds, and use the process of dipping and padding to preliminarily shape the soaked woven fabric through a padder. The shaped fabric passes through a setting machine with a drying time of 1 minute and a speed of 4m / min. Place the fabric that has passed the setting machine in a dry and dark place to regain moisture for 1 hour.

[0088] Test: The whiteness of the woven fabric after moisture regain is tested, followed by tests on hydrophilicity, mechanical properties, etc.

[0089] Hydrophilicity test: Fix the recovered fabric sample on the stretching ring, use a rubber-tipped dropper to drop a drop of water 1 cm above the fabric surface, and start timing. When the water drop is reduced to a non-reflective watermark, stop timing. Hydrophilicity can also be expressed by the water contact angle of the fabric after padding process.

[0090] Under the same padding process, the water absorption time is compared. The longer the water absorption time, the worse the water absorption.

[0091] Mechanical properties test: tear strength is tested according to GB / T 3917.1 standard using a drop weight fabric tear tester; sliding friction is tested according to GB / T 3925-2009 standard using a friction coefficient tester; breaking strength is tested according to ASTM D638 standard using a universal material testing machine.

[0092] Whiteness test: Place the fabric after moisture regain after rolling on the colorimeter for whiteness test. Fold the fabric into four layers and test four times. The average of the four values ​​is automatically read.

[0093] Antistatic test: Use a resistive static tester. Preheat the instrument before testing. Cut the woven fabric into 45mm×45mm after padding. Place it in an environment with a humidity of 29.6% RH and a temperature of 20.2℃ for 5 hours before testing.

[0094] The performance test results of the fabric treated with the emulsion prepared by the ether-modified single-terminal bis-hydroxyalkylamine polysiloxane (I) are shown in Table 3. R2O-1 to R2O-5 represent the sample numbers of the ether-modified single-terminal bis-hydroxyalkylamine polysiloxane (I) with different molecular weights.

[0095] Table 3 Ether bond modified single-terminal bishydroxylamine polysiloxane (I) emulsion application performance test Note: The original fabric in the table refers to the woven fabric without any treatment.

[0096] The static water absorption time of the fabric treated with the emulsion of ether-modified single-terminal bis-hydroxyalkylamine polysiloxane (I) is in the range of 10-25s. The hydrophilicity is compared with the static water absorption time of the original fabric of 180s. It can be seen that the emulsion of ether-modified single-terminal bis-hydroxyalkylamine polysiloxane (I) shows good hydrophilicity when applied to fabrics.

[0097] The softness rating of the fabric treated with the emulsion of ether-modified single-terminal bis-hydroxylamine polysiloxane (I) is 2.7-3.6. Compared with the original fabric 2.0, the softness is improved to a certain extent. Compared with the same series of ether-modified single-terminal bis-hydroxylamine polysiloxane (I), the ether-modified single-terminal bis-hydroxylamine polysiloxane (I) with a molecular weight of Mn~3000g / mol has the best softness and anti-fracture performance. The whiteness performance is better when the molecular weight is slightly larger (molecular weight Mn~5000g / mol).

[0098] Application Example 2

[0099] The double-terminal bishydroxylamine polysiloxane (II) prepared in Example 2 was prepared into an emulsion according to Application Example 1, and the performance test results after treating the fabric are shown in Table 4. R2O -1~D R2O -4 represents the sample number of ether-modified double-terminated bis-hydroxyalkylamine polysiloxane (II) with different molecular weights.

[0100] Table 4 Ether bond modified double-terminal bishydroxylamine polysiloxane (II) emulsion application performance test

[0101]

[0102] Note: The original fabric in the table refers to the woven fabric without any treatment.

[0103] The static water absorption time of the fabric treated with the emulsion of ether-modified double-terminal bis-hydroxylamine polysiloxane (II) is less than 10s, and the emulsion shows good hydrophilicity when applied to the fabric. The softness of the fabric treated with the emulsion of ether-modified double-terminal bis-hydroxylamine polysiloxane (II) is improved to a certain extent by 2.6-3.5.

[0104] The viscosity of ether-modified double-terminal bis-hydroxylamine polysiloxane (II) is low, and the emulsification process is faster, but the difficulty of emulsion preparation increases with the increase of molecular weight. The emulsification process of molecular weight 4000 is more difficult. From the perspective of uniformly emulsified emulsions, the sample emulsions of ether-modified double-terminal bis-hydroxylamine polysiloxane (II) with a molecular weight of 1000-4000 g / mol showed good hydrophilicity, anti-fracture ability and whiteness when applied to fabrics.

[0105] Application Example 3

[0106] The ether bond modified side chain bishydroxylamine modified polysiloxane (III) prepared in Example 3 was prepared into an emulsion according to Application Example 1, and the performance test results after treating the fabric are shown in Table 5. R2O -1~S R2O -5 represents the sample number of ether bond-modified side chain bishydroxyalkylamine-modified polysiloxane (III) using side chain hydrogen-containing silicone oils with different hydrogen contents (hydrogen contents are 0.09, 0.16, 0.21, 0.28 and 0.75% respectively).

[0107] Table 5 Application performance test of side chain ether bond modified bishydroxylamine polysiloxane (III) emulsion

[0108]

[0109] Note: The original fabric in the table refers to the woven fabric without any treatment.

[0110] The side chain ether bond modified bishydroxyamine polysiloxane (III) has a higher chance of bonding with fabrics, has good hydrophilicity, and has better softness and fracture resistance than single-end and double-end modified bishydroxyamine polysiloxanes, but its whiteness is slightly reduced.

[0111] Application Example 4

[0112] The carboxyl-containing single-terminated bishydroxyalkylamine polysiloxane (I-1) prepared in Example 4 was prepared into an emulsion according to Application Example 1. The performance test results after treating the fabric are shown in Table 6. CO2H-1 to CO2H-4 represent the product numbers of the emulsifiable multi-functional group-modified single-terminated bishydroxyalkylamine polysiloxane (I-1) having functional groups such as ether bonds and carboxyl groups obtained by reacting the raw materials of ether-modified single-terminated bishydroxyalkylamine polysiloxane (I) with glutaric acid at different molecular weights.

[0113] Table 6 Application performance test of carboxyl and ether bond modified single-terminal dihydroxylamine polysiloxane (IV) emulsion

[0114]

[0115]

[0116] Note: The original fabric in the table refers to the woven fabric without any treatment.

[0117] Judging from the properties of fabrics treated with the emulsion of carboxyl and ether bond modified single-terminal dihydroxyalkylamine polysiloxane (IV), the sample emulsion with a molecular weight of ~2500g / mol showed good hydrophilicity, anti-fracture ability and whiteness when applied to fabrics.

[0118] Application Example 5

[0119] The carboxyl-containing double-terminated bishydroxyalkylamine polysiloxane (II-1) prepared in Example 5 was prepared into an emulsion according to Application Example 1. The performance test results after treating the fabric are shown in Table 7. CO2H -1~D CO2 H-5 represents the product number of the emulsifiable multifunctional group-modified single-terminated bishydroxyalkylamine polysiloxane (II-1) having both ether bonds and functional groups such as carboxyl groups, obtained by reacting the ether-modified double-terminated bishydroxyalkylamine polysiloxane (II) raw materials of different molecular weights with glutaric acid.

[0120] Table 7 Application performance test of carboxyl and ether bond modified double-terminal bishydroxylamine polysiloxane (II-1) emulsion

[0121]

[0122] Note: The original fabric in the table refers to the woven fabric without any treatment.

[0123] The fabric was treated with a multifunctional group-modified double-terminated bishydroxyalkylamine polysiloxane (II-1) emulsion. The sample emulsion with a molecular weight of ~2000g / mol showed good hydrophilicity, anti-fracture ability and whiteness when applied to the fabric.

[0124] In summary, the fabrics treated with the emulsion of bishydroxyalkylamine polysiloxane modified with ether bonds and multifunctional groups in Application Examples 1 and 2 have high comprehensive performance. While the softness is improved, the hydrophilicity, anti-fracture ability and whiteness can all show good application performance.

[0125] Application Example 6

[0126] The single-terminal bishydroxylamine polysiloxane (IV) prepared in Comparative Example 1 without ether bond modification was prepared into an emulsion according to Application Example 1. The softness and hydrophilicity of the single-terminal bishydroxylamine polysiloxane (I) with ether bond modification and the single-terminal bishydroxylamine polysiloxane (IV) without ether bond modification in Example 1 were as follows: Figure 8 and Fig. 9 shown. Figure 8 The blue data corresponds to the softness of the ether-bonded single-terminated bishydroxyalkylamine polysiloxane (I) prepared in Example 1, and the red data corresponds to the softness of the single-terminated bishydroxyalkylamine polysiloxane (IV) prepared in Comparative Example 1 without ether-bond modification.

[0127] Fig. 9 The red part is the hydrophilicity data of the single-terminal bishydroxylamine polysiloxane (I) prepared in Example 1, and the red part is the hydrophilicity data of the single-terminal bishydroxylamine polysiloxane (IV) prepared in Comparative Example 1 without ether bond modification, which proves that the softness and hydrophilicity of the ether bond modified single-terminal bishydroxylamine polysiloxane are significantly improved compared with the single-terminal bishydroxylamine polysiloxane without ether bond modification.

Claims

1. A dihydroxyhydroxylamine-modified polysiloxane, characterized in that: Having a structure as shown in any one of Formulas I-III: Among them, R1 is * represents the site of connection with Si, n is a natural number of 8-64, m is a natural number of 20-50, and x: (162+60x+74y)=0.09-0.75%.

2. A carboxyl-containing bishydroxylamine-modified polysiloxane, characterized in that: Having a structure as shown in any one of formulas I to III as claimed in claim 1: Among them, R1 is * represents the connection site with Si, and n, m, x, and y are as described in claim 1.

3. The bishydroxyhydroxylamine-modified polysiloxane according to claim 1 or 2, characterized in that: The number average molecular weight of the polysiloxane represented by formula I is 1000 to 5000 g / mol, and the PDI value is 1.6 to 2.4; The number average molecular weight of the polysiloxane represented by formula II is 2000 to 4000 g / mol, and the PDI value is 1.90 to 2.50; The number average molecular weight of the polysiloxane represented by formula III is 500-5000 g / mol, and the PDI value is 1.6-3.

2.

4. The method for preparing a bishydroxyhydroxylamine-modified polysiloxane according to claim 1, characterized in that: Includes steps: Step 1, reacting allyl glycidyl ether with any hydrogen-containing polysiloxane represented by any one of M1-M3 to perform a hydrosilylation reaction to obtain any one of the intermediates M4-M6; Step 2, reacting any compound among the intermediates M4-M6 with 2-ethylaminoethanol to obtain the dihydroxyhydroxylamine-modified polysiloxane; Where R2 is * represents the connection site with Si, and n, m, x, and y are as described in claim 1.

5. The method for preparing a bishydroxyhydroxylamine-modified polysiloxane according to claim 4, characterized in that: In step 1, a Custer catalyst is added to catalyze the reaction, and the effective amount of palladium in the Custer catalyst is 5 to 30*10 of the total mass of the raw material. -6 ppm; Before the reaction, the Custer catalyst and allyl glycidyl ether were mixed and activated at 50-80°C for 15-40 minutes; The hydrosilylation reaction temperature of step 1 is 60-80°C and the reaction time is 6-8h; The reaction in step 2 is carried out at 80-120° C. for 2-8 hours; In step 1, the molar ratio of the double bond in allyl glycidyl ester to the silicon-hydrogen bond in the hydrogen-containing polysiloxane represented by any one of M1 to M3 is 1-1.2:

1.

6. The method for preparing the carboxyl-containing bishydroxyhydroxylamine-modified polysiloxane according to claim 2, characterized in that: The method comprises the steps of: reacting the dihydroxyhydroxylamine-modified polysiloxane according to claim 1 with glutaric anhydride to obtain the carboxyl-containing dihydroxyhydroxylamine-modified polysiloxane.

7. The method for preparing the carboxyl-containing bishydroxyhydroxylamine-modified polysiloxane according to claim 6, characterized in that: The reaction temperature is 80-120°C and the reaction time is 2-8h; The molar ratio of the R1 group to glutaric anhydride in the dihydroxyhydroxylamine-modified polysiloxane is 1:2-3.

8. A modified polysiloxane emulsion, characterized in that: Obtained by emulsifying the modified polysiloxane according to claim 1 or 2.

9. The method for preparing the modified polysiloxane emulsion according to claim 8, characterized in that: The method comprises the following steps: mixing 1-5 parts of the modified polysiloxane, 0.1-2 parts of the composite catalyst, 0.01-0.5 parts of acetic acid and 5-15 parts of the modified polysiloxane for phase inversion; diluting the emulsion after phase inversion with water at a mass ratio of 5-15:200 to obtain the modified polysiloxane emulsion; The composite catalyst is a mixture of AE0-6 and AEO-9, and the mass concentration of acetic acid is 20-40%.

10. The use of the modified polysiloxane emulsion according to claim 8 as an organosilicon softener in fabrics, characterized in that: The method comprises the following steps: immersing the fabric in the modified polysiloxane emulsion for 5-30 seconds, and obtaining softened fabric through shaping and drying.

Citation Information

Patent Citations

  • Soft laundry gel ball, and preparation method and application thereof

    CN106544173A

  • Double-end carboxylalkyl-terminated polysiloxane containing carboxyl ether group structure, and preparation method thereof

    CN113388114A

  • Amino-functional polysiloxanes

    EP1361245A1